Roleplaying in EFL Classroom: EFL learner’ Oral Proficiency Achievement and Perception - Jaya Nur Iman; Nike Angraini (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2022)
This research was aimed at inquiring the application of roleplay toward the EFL learners’ oral proficiency achievement. An experimental design, primarily on the pre-experimental design, was used in this research. Thirty-eight university students were taken conveniently as the research sample. A test and a close-ended questionnaire were administered to rate the oral proficiency achievement and perception of the EFL learners. The findings revealed that (1) the oral proficiency achievement level (OPAL) of the EFL learners in the experimental group was in the good and very good achievement level, (2) there was a significant improvement on the EFL learners’ OPA after the intervention given, and (3) then positive perception made by the EFL learners about the application of roleplay on their achievement of oral proficiency. In concluding, using roleplay made a significant improvement on the EFL learners’ oral proficiency achievement. This research also provides pedagogical implication for lecturers, students, stakeholders, and near future researchers to apply this as the alternative instructional activity to develop the oral proficiency of the English language learners.